Effect of acid concentration and time on synthesizing the titanium dioxide from synthetic rutile waste - Huzaikha Awang; Ahmad Mukifza Harun; Shahril Yusof; Clarence M. Ongkudon; Eddy Mohd Farid Mohd Yusslee (Paper Publications, 2017)
A fast and easy method for preparing the titanium dioxide (TiO2), using a caustic hydrothermal decomposition conditions followed with sulphate process using sulfuric acid (H2SO4) are presented. The effects of acid concentration and treatment time of sulphate process to the TiO2 growth were focused in this research. The chemical composition of the product will be characterized using Electron Dispersive (EDX), the morphology and growth of titanium were analysed using a Field Emission Scanning Electron Microscope (FESEM) and the crystallinity of sample were analysed by X-Ray Diffraction (XRD). From this research work, we found that the caustic hydrothermal decomposition method followed with sulphate process has been proven to extract a titanium nanocrystals with the average mean size < 100nm after treated with medium acid concentration and short treatment time.